Motherhood penalty: The Brazilian peculiarity - Francis Petterini; Jeniffer Gonçalves (Societal Impacts)
In this study, we investigate the motherhood penalty in Brazil by tracking mothers in administrative databases from the years before to after the birth of the child. In particular, we analyze the wage trajectories using econometric models to estimate the counterfactuals if these women had not been mothers. In doing so, we have to take into account a Brazilian peculiarity: there is a government policy that allows mothers to opt for self-employment in order to spend more time with their children. After adapting our modeling to this specificity, the estimated wage losses of mothers are around 25% and 10% when the children are of infant and school age, respectively. The message in terms of social impact is that it is necessary to help mothers to return to the labor market after childbirth under the same conditions and with the same opportunities for professional development as before pregnancy. We believe that this support can be provided, for example, through better childcare policies in society.